Facilitation and biodiversity jointly drive mutualistic networks. (2nd February 2021) - Losapio, Gianalberto; Norton Hasday, Elizabeth; Espadaler, Xavier; Germann, Christoph; Ortiz‐Sánchez, Francisco Javier; Pont, Adrian; Sommaggio, Daniele; Schöb, Christian
Abstract: Facilitation by nurse plants increases understorey diversity and supports ecological communities. In turn, biodiversity shapes ecological networks and enhances ecosystem functioning. However, whether and how facilitation and increased biodiversity jointly influence community structure and ecosystem functioning remains unclear. We performed a field experiment disentangling the relative contribution of nurse plants and increasing understorey plant diversity in driving pollination interactions. Both the presence of nurse shrubs and increased understorey plant diversity increased pollinator diversity and visitation rates. While nurse and understorey diversity effects on pollinator visitation rates did not interact, the effects of increasing understorey plant diversity on pollinator diversity were stronger in the absence than in the presence of shrubs, meaning that nurse shrubs attenuated the effects of high understorey diversity and buffered the effects of low understorey diversity. We also found positive complementarity effects among understorey species as well as complementarity between nurse plants and understorey species at high diversity. Results also indicate negative selection effects, suggesting that species with generally few pollinators benefit the most in the polyculture while a species (possibly the nurse plant) with generally lots of pollinators does not. The corresponding changes in pollination networks with the experimental treatments were due to both changes in the frequency of visits and turnover in pollinator community composition. Synthesis . Plant–plant facilitative systems, where a nurse plant increases understorey plant diversity, are common in stressful environments. Here, we show that these facilitative systems positively influence mutualistic interactions with pollinators via both direct nurse effects and indirect positive effects of increasing plant diversity. Conserving and supporting nurse plant systems is crucial not only for maintaining plant diversity but also for supporting ecosystem functions and services. Abstract : On one side, facilitation between plants promotes biodiversity and supports the structure of ecological networks; on the other, richness of plant and insect species increases ecosystem functions. However, we still don't know the direct and indirect contribution of facilitation and biodiversity to ecosystem functioning and pollination networks. We conducted a field experiment to show how facilitation by nurse plants and understorey diversity synergistically increase pollinator diversity and support mutualistic networks, revealing a novel mechanism underlying the consequences of biodiversity change. Photo credit: Elizabeth Norton Hasday.